Penggunaan Media Realita untuk Meningkatkan Hasil Belajar Siswa dalam Pembelajaran Matematika Kelas 1 SDN 005 Sunhai Alah - Ismearti Ismearti (el-Ibtidaiy:Journal of Primary Education, 2020)
This study aims to increase mathematics learning outcomes by using reality media for grade 1 students of SDN 005 Sunhai Alah, Kecamatan Hulu Kuantan in 2018/2019. Research is a class action research with three cycles, each cycle consisting of planning, implementation, evolution and reflection. Data collection techniques and tools in this study used descriptive analysis techniques for data that contained student work documents, a list of grades and an observation sheet. The results show what is meant by learning outcomes using reality media. Before the action, only 38% of students met the minimum completeness criteria. In cycle I Is an increase in student learning outcomes that is 53% of students reach the minimum completeness criteria. Furthermore, the second cycle of student learning outcomes increased to reach 74% of students achieving the minimum completeness criteria. Then cycle III 100% of students reach the minimum completeness criteria. Can be used to prove the use of reality media to improve student learning outcomes in mathematics learning at grade 1 SDN 005 Sunhai Alah, Kecamatan Hulu Kuantan.